Development of sets-based science e-module to improve critical thinking skills of grade viii students on additive and addictive substances material - Asifa Khoirun Nisa; Diah Wahyuni; Sri Wahyuni; Firdha Yusmar; Rizka Elan Fadilah (Biology Education Department, IKIP Budi Utomo, Malang, Indonesia, 2022)
The critical thinking skills of junior high school students in Jember are still low, the existing learning is still teacher-centered, and the students lack initiative in asking questions. Based on the results of the national examination of additives and addictive substances, in the last five years, it is relatively low. Through these data, it is known that there are problems related to critical thinking, namely additives and addictive substances. The research aims to develop a SETS-based (Science, Environmental, Technology, and Society) science e-module on additive and addictive substances material to improve students’ critical thinking skills. This type of research is Research and Development (R&D) uses a 4D development model. The SETS-based science e-module on additive and addictive substances material developed was tested on research subjects, namely 23 students of class VIII-I, SMP Negeri 1 Jember. The research instruments include validation sheets, learning implementation sheets, pre-test, and post-test questions, and response questionnaires. The validation result of the development of SETS-based science e-module on additive and addictive substances material was stated as valid, with a score of 79%. The practicality of learning was stated with a score of 3.64%, with a very practical category. The N-gain test score of 0.81 with a high category, so that the SETS-based science e-module on additive and addictive substances material can improve students’ critical thinking skills. The results of the student's response questionnaires obtained a score of 89% in the very good category. Based on these data, the development of SETS-based science e-module on additive and addictive substances improves students’ critical thinking skills.